Billedprogrammet på Trondenes: Den hellige Anna – sjømennenes og rikdommens beskytter - Bergesen, Rognald Heiseldal (Nordlit, 2015)
The interior of the parish church at Trondenes in Harstad in Northern Norway is one of the best-preserved medieval interiors in Scandinavia. Four of its reredos have survived, three of them in situ. A significant characteristic of the decoration in the church is the pronounced presence of St. Anne and the Holy Kinship. The article explores the roles of these motifs in the iconography at Trondenes. Even though there are no sources related to the specific religious use of these motifs at Trondenes, our general knowledge of their cult elsewhere in Europe suggests how they might have been used in Trondenes. Among ordinary people in the medieval Northern Germany, the cult of Saint Anne and the Holy Kinship were related to the protection of sailors and to secure the growth of their income, as well as to protect against diseases. Usually these motifs were found in maritime, urban regions. St. Anne was regarded as a role model for the middle class women, and the Holy Kinship as a “self-image” of the trading middle class. Trondenes is the main Church in a large maritime region. In the late middle ages the fisheries along the coastline provided large incomes to the chapter of the Cathedral of Nidaros who owned Trondenes and to the local merchants at Trondenes. In such circumstances it is reasonable that the presence of St. Anne and the Holy Kinship at Trondenes was related to the protection of local sailors and to the growth of income from the fisheries.